Atmospheric Carbon Dioxide Modifies the Antimicrobial Activity and Oxidative Stress Generated by Ciprofloxacin in Escherichia coli - Viviana Cano Aristizábal; Elia Soledad Mendoza Ocampo; Melisa de los Ángeles Quinteros; María Gabriela Paraje; Paulina Laura Páez (Pathogens)
The accelerated increase in atmospheric CO2 concentration is one of the most pressing problems at present. It is possible that this increase causes slight modifications in intracellular CO2. The aim of this work was to determine whether CO2 at different concentrations can affect the oxidative damage caused by ciprofloxacin (CIP) in Escherichia coli and to evaluate the possible implications of this effect for human health. To identify the effects of CO2 on the action of CIP, reactive oxygen (ROS) and reactive nitrogen (RNS) species were measured at two different CO2 concentrations while monitoring the bacterial antioxidant response. These assays showed that CO2 led to a decrease in ROS formation relative to that under atmospheric conditions (ACs), while it had the opposite effect on RNS formation, which increased relative to that under ACs. Under CO2 conditions, antioxidant defenses were less activated, with superoxide dismutase, catalase, and ferric reducing assay potency decreasing compared to those under ACs; however, reduced glutathione exhibited the opposite behavior. In the presence of CO2, the activity of CIP against E. coli was reduced relative to that under ACs. In conclusion, CO2 interferes with the action of CIP in bacterial cells, generating changes in oxidative stress.